2004
DOI: 10.1007/s00436-003-1024-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and specificity of a 38�kDa Loa loa antigenic fraction in sera from high-microfilaraemic Gabonese patients

Abstract: Circulating antigens isolated from sera of three high-microfilaraemic ( Loa loa) Gabonese patients were fractionated by gel filtration. A major component (38 kDa) was identified after SDS-PAGE and immunoblotting using sera of amicrofilaraemic patients with high level of antimicrofilariae Loa loa antibodies. The 38 kDa fraction was not found in the sera of parasitised patients or healthy controls. We looked for the 38 kDa antigen in the various stages of the filarial life cycle and found it in extracts of Loa l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Loa loa -specific antibodies were detected in serum samples from patients by indirect immunofluorescence (IIF) with homologous antigens from L. loa microfilariae prepared in the department, as described elsewhere (Walker-Deemin et al , 2004). The antibody– L. loa specificity threshold was a titre above 1:200.…”
Section: Methodsmentioning
confidence: 99%
“…Loa loa -specific antibodies were detected in serum samples from patients by indirect immunofluorescence (IIF) with homologous antigens from L. loa microfilariae prepared in the department, as described elsewhere (Walker-Deemin et al , 2004). The antibody– L. loa specificity threshold was a titre above 1:200.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement of Loaspecific IgG 4 in an ELISA may be used to detect an occult infection (Akué et al, 1994) but this technique is not very sensitive (Touré et al, 1999a;Klion et al, 2003). Although circulating Loa antigens have been detected in some patients, no diagnostic tests based on antigen detection are currently available (Walker-Deemin et al, 2004). The best technique currently available for the diagnosis of loiasis, especially occult infection, is based on a PCR for the detection of the species-specific sequences of the repeat-3 region of the gene encoding a 15-kDa protein (Touré et al, 1997(Touré et al, , 1998.…”
Section: Diagnosismentioning
confidence: 99%
“…Several prior studies have reported circulating L . loa antigens in the blood [32–34] and urine [35] of persons with loiasis. Our study differed in that we sought to specifically capture the antigens responsible for W .…”
Section: Discussionmentioning
confidence: 99%